Synthesis of thin protective coatings from ionizing radiation based on polymer template - Калиекперов, М.Е.; Козловский, А.Л.; Кадыржанов, К.К. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this paper, we consider the preparation of thin-film coatings based on copper by electrochemical analysis. The mean free path has been theoretically calculated and the absorption efficiency has been defined using experimental data on the screening of heavy ions.